Proceedings of the 18th Online World Conference on Soft Computing in Industrial Applications (WSC18) - Ane, Bernadetta Kwintiana; Cakravastia, Andi; Diawati, Lucia (Advances in Intelligent Systems and Computing, 2019)
This book gathers the papers presented at the 18th Online World Conference on Soft Computing in Industrial Applications (WSC18), which was held on 1-12 December 2014 on the World Wide Web. The conference is open to all academics, students and industrial/commercial parties, and is hosted online between authors and participants over the Internet. The 2014 installment of the Online World Conference on Soft Computing in Industrial Application consisted of a selected keynote speech, invited talks, tutorials, special sessions, and general track papers. The program committee received a total of 51 submissions from 12 countries, reflecting the international nature of the event. Each paper was peer-reviewed (typically by 3 reviewers), culminating in the acceptance of 20 papers for publication.